Soil physical quality indices of mining-induced disturbances in soil within the Loess region of western China - Yang, Dejun; Bian, Zhengfu; Zhang, Yajun; Yu, Haochen; Wu, Zhenhua (Journal of Environmental Engineering and Landscape Management, 2024)
Soil sampling and in situ measurements were conducted at 24 locations at three time points from May 2015 to April 2016. The statistical analysis showed that the variabilities of soil water content and soil penetration were moderate, while particle size and soil saturated hydraulic conductivity varied considerably. Rainfall before measurements contributed positively to the mean soil water content and negatively to particle size. This was mainly due to the soil aggregates and large soil particles being broken into smaller particles from rain splash. The detached small-sized soil particles could coalesce into larger-sized ones and even soil aggregates. Stressors in zones differ, resulting in variations between soil physical quality indices. The point-to-point comparisons indicated that the mean measured soil water content and soil saturated hydraulic conductivity were similar, if the measurements for these two indices were conducted under similar weather conditions during the same period between years. The investigation on the relationships among soil physical quality indices showed a negative relationship between the measured soil water content and soil saturated hydraulic conductivity. A positive correlation was also found between soil particle size and soil saturated hydraulic conductivity. Lower soil strength resulted in higher soil saturated hydraulic conductivity.